2023
DOI: 10.3390/plants12132427
|View full text |Cite
|
Sign up to set email alerts
|

Radial Increment of Beech (Fagus sylvatica L.) Is under a Strong Impact of Climate in the Continental Biogeographical Region of Croatia

Abstract: European beech (Fagus sylvatica L.) is an important component of forests in the alpine and continental biogeographical regions of Croatia. This study aimed to (1) analyze the long-term response of beech to climate, (2) identify potentially critical climatic conditions that could negatively affect the radial increment (RI) and vitality of beech, and (3) evaluate differences in the response of beech between the two biogeographical regions in Croatia. We used the 16 × 16 km Croatian ICP Forests Level 1 network. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The observed decreasing trend for common beech ( Figure 3 ) was highly significant, even when compared to the data from the other investigated deciduous species. The sensitivity of beech to drought is well known [ 36 , 55 , 56 , 57 ]. Our findings indicated that after the droughts in 2000 and 2003, the RBAI decreased to a value under 2% and has not recovered yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decreasing trend for common beech ( Figure 3 ) was highly significant, even when compared to the data from the other investigated deciduous species. The sensitivity of beech to drought is well known [ 36 , 55 , 56 , 57 ]. Our findings indicated that after the droughts in 2000 and 2003, the RBAI decreased to a value under 2% and has not recovered yet.…”
Section: Discussionmentioning
confidence: 99%
“…We selected years with total summer precipitation (for June, July, and August) lower than normal in more than 90% of the total ICP Forests Level I plots. In subsequent analyses, we closely examined tree growth in the years 1990,1992,1993,1994,2000,2003,2012,2013,2015,2017,2019, and 2022 (Figure 2), many of which were used as negative pointer years in other recent European studies [36]. Map of active ICP Forests Level I plots and plots included into the analysis.…”
Section: Site and Climatic Characteristicsmentioning
confidence: 99%